2022
DOI: 10.3991/ijet.v17i11.29061
|View full text |Cite
|
Sign up to set email alerts
|

The Camera-on or Camera-off, Is It a Dilemma? Sparking Engagement, Motivation, and Autonomy Through Microsoft Teams Videoconferencing

Abstract: A videoconferencing system to communicate synchronously is an indispensable tool for educators, teachers, students, parents, and administrators in online courses. One of the effective online learning platforms that can increase student engagement and motivation in online courses is Microsoft Teams. This research aimed to explore English as a Foreign Language (EFL) students’ views of enacting Microsoft Teams videoconferencing. This study employed a mixed-method design complemented by observation, open-ended que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The EFL students also confirmed that they frequently seek additional information regardless of English lessons to assist them in better understanding the course contents. This finding is in line with prior studies which confirm that online learning can promote learner autonomy (Muhammad, 2020;Rojabi, Setiawan, Munir, Purwati, & Widyastuti, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…The EFL students also confirmed that they frequently seek additional information regardless of English lessons to assist them in better understanding the course contents. This finding is in line with prior studies which confirm that online learning can promote learner autonomy (Muhammad, 2020;Rojabi, Setiawan, Munir, Purwati, & Widyastuti, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…In post-measures, students who received instruction through the LMS demonstrated improved listening skills. Additionally, students in the control group-where instruction is given in a conventional manner-showed less advancement in their language proficiency [60].…”
Section: Resultsmentioning
confidence: 98%
“…Imagine reading a story on Wattpad and encountering a sentence structure you haven't seen before. Curiosity might lead you to ask a question in the comments, sparking a discussion about its effectiveness and the grammar rules behind it (Rojabi et al, 2022). This interactive dialogue, enriched by constructive feedback from other users, becomes a mini-grammar lesson, expanding your understanding of language and its nuances (Watsons and Newman., 2021).…”
Section: ''The Advanatage Is We Can Be Able To Enhance Our Reading Sk...mentioning
confidence: 99%